Analisis Pengaruh Kreativitas dan Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha di Pajak Melati Medan - Wahyudi, Rifky; Siregar, M. Yamin (Mahesa Research Center, 2025)
This study was conducted with the aim of determining the effect of Creativity and Entrepreneurial Knowledge on Entrepreneurial Interest in Pajak Melati Medan. This type of research is descriptive quantitative, namely a study that aims to explain an empirical phenomenon accompanied by statistical data, characteristics and relationships between variables whose data collection techniques use questionnaires. Data collection in this study was carried out by distributing questionnaires using a Likert scale. The sample of this study was 68 respondents from Pajak Melati Medan entrepreneurs. The method used in data collection is the non-probability sampling technique, the analysis uses multiple linear regression analysis with the help of the SPSS 25 program. The results of this study indicate that between the two dimensions of Creativity and Entrepreneurial Knowledge, there is an influence on Entrepreneurial Interest in Pajak Melati Medan. The R2 value of the equation is 47.5, meaning that the variable of entrepreneurial interest (dependent) that can be explained by the variables of creativity and entrepreneurial knowledge (independent) in this study is 47.5 while 53.6% is influenced by other variables not explained by this study.